Energy Flux and Animal Products - Emmanuel, B. S. (Obafemi Awolowo University Press, 2013)
The production of food is a process of energy transformation - changing energy from, an inedible into an edible form: Different foods vary .in the energy required to .make them fully edible. Energy use in food production has been increasing faster than its use in many other sectors of the world economy and has become an overriding factor in food production distribution and consumption. Today, the source and use of energy are key issues in every area of human endeavor Agriculture is unique 'because one of its-major energy sources is the sun..